Redescription of Wallinia brasiliensis (Digenea: Allocreadiidae) from Astyanax lacustris (Osteichthyes: Characidae) in Brazil - Narciso, Rodrigo Bravin [UNESP]; Vieira, Diego Henrique Mirandola Dias [UNESP]; Dias, Karina Gabriele Alves [UNESP]; Abdallah, Vanessa Doro; da Silva, Reinaldo José [UNESP] (Springer Nature, 2022)
The allocreadiid trematode Wallinia brasiliensis Dias, Müller, Almeida, Silva, Azevedo, León & Abdallah, 2018 is redescribed herein based on integrative taxonomy approach using morphological and molecular data from seven adult specimens found in the digestive tract of the yellow-tail lambari, Astyanax lacustris (Lütken, 1875), sampled in Pardo River, municipality of Botucatu, São Paulo State, Brazil. The present specimens are about four times longer and show several morphological differences (e.g. distribution of vitelline follicles and in the number and relative size of operculate eggs) regarding type-species from Batalha River (type locality), São Paulo State, Brazil. Considering that some of the diagnostic features listed in the original description of W. brasiliensis were lost/modified in the present specimens, we conclude that there is a need to redescribe this species and to perform a new comparison between W. brasiliensis and its five congeners (including two species not yet described at the time of the original description). Based on the new data, W. brasiliensis can be readily distinguished from its congeners by the combination of the oblique position of testes, the extension of vitelline follicles, and the size of the body and internal organs. The validity of the identification of the present specimens as W. brasiliensis was confirmed by the molecular characterization of the LSU rDNA gene, which showed 100% similarity between the original and current sequences. A key to the six known species of Wallinia Pearse, 1920 is provided.
Keywords: 28S rDNA; Freshwater; Neotropical; Pardo River; Taxonomy; Trematode